2017
DOI: 10.1177/1476750317723965
|View full text |Cite
|
Sign up to set email alerts
|

Patient involvement 2.0: Experience-based co-design supported by action research

Abstract: Strong professionals who influence the development of healthcare services have dominated healthcare organizations for many years. However, this dominance has been challenged recently through patient involvement. One method of achieving patient involvement is experience-based co-design (EBCD), in which patients and healthcare professionals work together to improve care. Patient involvement has considerable potential, but also presents certain challenges. This article addresses these challenges using experiences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(82 citation statements)
references
References 35 publications
1
77
0
Order By: Relevance
“…Process evaluation data were available for eight studies, with evaluation for Gustavsson’s neonatal and diabetes studies reported together 27. Both service users and service providers had positive views of the EBCD process26 28 29 and reported that specific, measurable, achievable, relevant, time-bound goals reflected their service improvement needs 29.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Process evaluation data were available for eight studies, with evaluation for Gustavsson’s neonatal and diabetes studies reported together 27. Both service users and service providers had positive views of the EBCD process26 28 29 and reported that specific, measurable, achievable, relevant, time-bound goals reflected their service improvement needs 29.…”
Section: Resultsmentioning
confidence: 99%
“…Participants in the Tsianakas cancer study24 stated that the collaborative nature of EBCD gave service users a greater sense of direct responsibility for the work and its outcomes built a strong relationship between service users and service providers and noted a higher level of clinical engagement in the improvement effort than is usually observed in other projects. Service user participants from the Gustavsson’s neonatal and diabetes studies27 reported that the diversity of views, when presented face-to-face, resulted in a common perspective of patient processes. Participants also noted that the power relationship between professionals and patients was more equal in the EBCD than in actual care relationships.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 It is argued that to meaningfully involve patients, involving them as equal partners in a knowledge co-creation process could be helpful. 10 This process consists of three steps: first, patients' implicit knowledge is made explicit (knowledge articulation); integrated with that of researchers and health professionals (knowledge integration) and sustainably implemented in healthcare innovations (knowledge embedment). In many cases, patients have difficulties in articulating their needs and ideas due to limited medical knowledge or being unable to think at a more abstract level.…”
Section: Introductionmentioning
confidence: 99%
“…The patient and family experience is an important source of knowledge ( 4 ) and central to improving care and creating sustainable health care systems for the future ( 5 , 6 ). Improved service efficiency has been linked to improvements in patient experience ( 1 ), and research has demonstrated links between patient satisfaction and health professional satisfaction ( 7 ).…”
Section: Introductionmentioning
confidence: 99%